2016
DOI: 10.1109/lawp.2015.2430284
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Dielectric Nanocomposite for Antenna Miniaturization and SAR Reduction

Abstract: A 900 MHz meander PIFA on a magneto-dielectric nanocomposite (MDNC) substrate for mobile communication is presented. Cobalt nanoparticles were synthesized with polymer matrix and its properties were measured up to 4GHz. Bandwidth, gain and radiation efficiency of antenna on different substrates (MDNC, High K material and FR4) were compared and it is demonstrated that MDNC is beneficial for antenna miniaturization with acceptable antenna performance. Head effects due to the antenna were studied and Specific Abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…R-cards were used in [9] where SAR reduction was achieved with degradation of radiation efficiency. Recently, magneto-dielectric nano composite materials as substrate were used in [10] to reduce the SAR. Although the use of the above techniques is successful in reduction of SAR, the design is complex, and the size of the antenna also increases.…”
Section: Introductionmentioning
confidence: 99%
“…R-cards were used in [9] where SAR reduction was achieved with degradation of radiation efficiency. Recently, magneto-dielectric nano composite materials as substrate were used in [10] to reduce the SAR. Although the use of the above techniques is successful in reduction of SAR, the design is complex, and the size of the antenna also increases.…”
Section: Introductionmentioning
confidence: 99%
“…33 Han et al demonstrated that the downsizing of an antenna can be achieved by using magneto-dielectric nanocomposite (MDNC) materials as substrate. 34 The proposed substrate was synthesized by mixing cobalt nanoparticles in fluoropolymer matrix. A Meander planar inverted-F antenna (PIFA) designed based on MDNC material is depicted in Fig.…”
Section: Antenna Applicationsmentioning
confidence: 99%
“…Microwave devices using magnetic materials. (a) Magnetic thin film-based microwave noise suppressor,24 (b) Meander planar inverted-F antenna (PIFA) on magneto-dielectric nanocomposite (MDNC) material,34 (c) magnetically tunable band-pass filters37 and (d) spintronic device as nanoscale microwave oscillator15 (modified and redrawn using the data from Refs. 24, 34, 37 and 15).…”
mentioning
confidence: 99%
“…It has an additional advantage that the permittivity can be controlled by varying the concentration of Barium Titanate in the composite [21][22][23][24]. Also, using similar chemical approaches, a composite can be prepared wherein permittivity and permeability of the material can be varied simultaneously, as demonstrated by various research groups [25][26][27][28]. Hence, with the use of these magneto-dielectric composites, it is possible to realize the GIM cloak for the current purpose.…”
Section: Simulations In S-bandmentioning
confidence: 99%